INVESTIGATION OF ATMOSPHERIC CORROSION OF LOW-CARBON STEEL IN KUALA TANJUNG BATU BARA - Affandi, Affandi; Nasution , Arya Rudi; Lubis , ‪Riadini Wanty; Tanjung, Iqbal; Ananda, Rizki; Huzni , Syifaul (Jurnal Rekayasa Mesin, 2025)
Corrosion is one of the most problematic issues in the material industry that may generate tons of drawbacks. In recent years, Kuala Tanjung has experienced an increase related to the development of infrastructure including trestles and docks that are capable to accommodate mother vessels, containers, and stockpile tanks. The growth of industrial estate occurring would lead to a consideration that Kuala Tanjung might be possible to be an International Hub Port. Despite all these development efforts, the detrimental effects could lead to the quality of water, air, and soil caused by industrial waste and consequently the corrosion attack would easily occur. This condition is exacerbated by the lack of atmospheric corrosiveness data in Kuala Tanjung Batu Bara. Then, it is necessary to investigate the corrosion rate using the weight loss method and refer to ASTM G – 1. Specimen dimensions and test racks are designed based on ASTM G – 50 standards. The aim of this study is to investigate the atmospheric corrosion rate of low-carbon steel and map the atmospheric corrosion in Kuala Tanjung, Batu Bara. The research site is divided to six locations, namely points A, B, C, D, E, and F. The Low-carbon steel test specimens conducted use elbow steel profiles, plates, and quadrangles. Testing is carried out for six months with data collected once every two weeks. The results of this study show that the corrosion rate values reach 0.0564 – 0.5230 mpy for elbow profiles, 0.0552 – 0.4984 mpy for plate profiles, and 2.1341 – 5.2022 mpy for quadrilateral profiles. These results indicate that the corrosion rate of low-carbon steel in the Kuala Tanjung is still relatively safe as well as the atmospheric corrosiveness maps can be created at each location.